A Model of State-Owned Asset Management Based on Pancasila Values: Achieving the Highest and Best Use - Koeswahyono, Imam (Arena Hukum, 2024)
This article discusses the formulation of a model called "Sustainable and Equitable Organization and Management of State/Region/Village-Owned Assets Based on the Pancasila". The authors introduce a “highest and best use” approach to state asset management, aiming to address gaps in existing norms around asset governance, particularly regarding the absence of a mechanism for asset management and dispute resolution. This condition can potentially bring about corruption through the exchange of state land assets that are unequal in value. The model initiated by the authors comes from the need to elaborate the legal politics of Pancasila into laws that specifically regulate the management of state assets with the principle of best utilisation oriented towards the greatest prosperity of the people. This conceptual research aims to formulate and develop a research model with the following outputs: a. to find a paradigm for agrarian legal research that is based on the critical agrarian approach in the perspective of legal science; b. to determine the integrity and harmony with the Pancasila philosophy, and the constitutionality of regulation and institutionalism, of the management of state/region/village-owned assets; c. to formulate an institutional model for conflict resolution in agrarian affairs, primarily for cases of conflict involving state/region-owned assets in the form of an agrarian court that can resolve and eliminate the backlog of cases of agrarian conflicts for both public and private aspects specifically, with legal certainty and justice. Achieving this goal requires establishing a State Asset Management Agency and the existence of an Agrarian Court. The weakness of this idea lies in the realization of forming regulations that need to be in harmony with related laws and regulations. This model is necessary for synergising the roles of legislators, stakeholders, and the public based on the principle of sustainable and just management of state assets according to Pancasila.